Home monitoring for COVID-19 - Medina, Michelle; Babiuch, Christopher; Card, Michelle; Gavrilescu, Ruthann; Zafirau, William; Boose, Eric; Giuliano, Kimberly; Kim, Alice; Jones, Robert; Boissy, Adrienne (Cleveland Clinic Journal of Medicine, 2020)
Cleveland Clinic recognized the importance of mitigating community transmission of COVID-19 by keeping people at home. Patient-care activities quickly pivoted to remote touches, preserving continuity through a variety of digital and telephonic modalities. As the number of confirmed cases grew, standardizing home-based care became critical to managing high-risk patients, moderating the risk of exposure for healthcare workers, and reducing the amount of community spread through appropriate education on home-based care for exposed or infected individuals. This novel, team-based approach to caring for patients with COVID-19 incorporates a self-monitoring app for patient engagement, monitors symptoms for early intervention, and promotes a holistic view of care.